Hearing outcome after myringoplasty in Sweden: A nationwide registry‐based cohort study. (20th February 2020) - Berglund, Malin; Olaison, Sara; Bonnard, Åsa; Fransson, Mattias; Hultcrantz, Malou; Florentzson, Rut; Dahlin, Christer; Eriksson, Per Olof; Westman, Eva
Abstract: Objectives: To present hearing results after successful primary myringoplasty surgeries registered in the Swedish Quality Registry for Myringoplasty and to evaluate the chance of hearing improvement and the risk of hearing loss. Design: A retrospective nationwide cohort study based on prospectively collected registry data between 2002 and 2012. Settings: Registry data from secondary and tertiary hospitals performing myringoplasty. Participants: Patients with healed tympanic membrane after primary myringoplasty surgery performed from 2002 to 2012 in Sweden. Main outcome measures: Postoperative hearing results, hearing gain and air‐bone gap (ABG). Results: In 2226 myringoplasties, air conduction audiograms were recorded, and the average preoperative pure tone average (PTA4 ) of the group was 28.5 dB, which improved postoperatively to 19.6 dB with an average of 8.8 dB improvement. Bone conduction was measured for 1476 procedures. Closure of the ABG to 10 dB or less was achieved in 51% of the ears and to less than 20 dB in 89% of the ears. Sixty‐one percent of patients with preoperatively deteriorated hearing experienced improved hearing, but 3% of all patients experienced deteriorated hearing. After the surgery, 93% of the patients were satisfied. Conclusions: Hearing results after successful myringoplasty surgery are often favourable, but although the tympanic membrane is healed, hearing improvement is not guaranteed, and hearing deterioration can also occur.